Review of Lex Paulson, Cicero and the People’s Will: Philosophy and Power at the End of the Roman Republic - Wildberger, Jula (Ciceroniana On Line, 2023)
Lex Paulson, Cicero and the People’s Will: Philosophy and Power at the End of the Roman Republic, Cambridge University Press, Cambridge (et al.) 2023.